PENGARUH PEMISAHAN LAYANAN BPJS DAN NON-BPJS, KUALITAS PELAYANAN MEDIS, DAN FASILITAS POLIKLINIK TERHADAP KEPUASAN PASIEN DI RS SWASTA TANGERANG - Mona Rahmadia,; Purwadhi, Purwadhi; Kahar Mulyani,; Erliany Syaodih, (Journal of Innovation Research and Knowledge, 2025)
This study investigates the impact of service separation, medical service quality, and polyclinic facilities on patient satisfaction in a private hospital in Tangerang. Based on a survey of 102 respondents, all three variables significantly affect satisfaction. The t-test results show significant effects for each variable (t = 4.127 to 7.695, p < 0.001), and the F-test confirms the model's overall significance (F = 33.900 for BPJS; F = 16.737 for non-BPJS, p < 0.001). Medical service quality and facilities are the most influential factors. Non-BPJS patients report higher satisfaction levels. These findings highlight the need for equitable service improvements across patient